Comparing the clinical and singleton neonatal outcomes in male infertility patients with Oligoasthenospermia, OA, or NOA following fresh ICSI-ET using different sources of sperm - Xu, Jianmin; Yang, Qingling; Chen, Wenhui; Jiang, Yuqing; Shen, Zhaoyang; Wang, Huan; Sun, Yingpu (Frontiers in Endocrinology, 2023)
Objective: To investigate clinical and singleton newborn outcomes in fresh cycles of embryo transfer after intracytoplasmic sperm injection (ICSI-ET) with diverse sperm sources (Ejaculate, Epididymis, and Testis) in patients with Oligoasthenospermia, obstructive azoospermia (OA) or non-obstructive azoospermia (NOA).Patients who received fresh ICSI-ET for the first time at the First Affiliated Hospital of Zhengzhou University Reproductive Medicine Center between June 2011 and June 2021 were selected for this 10-year retrospective cohort analysis. After propensity score matching, only 1630 cycles were included in the investigation of ICS-ET clinical and singleton newborn outcomes in patients with Oligoasthenospermia, OA, and NOA using sperm from diverse sperm sources.After propensity score matching, our data revealed a negligible difference in baseline and cycle parameters among groups. In patients with oligasthenospermia and OA, different sperm sources do not appear to influence clinical pregnancy rates and live birth rates, nor do they influence newborn outcomes, such as newborn weight, premature birth rate, and neonatal sex ratio in singleton births, except for OA patients who use epididymal sperm having higher low birth weight (LBW) rates in singleton pregnancies than those who use testicular sperm. In addition, clinical pregnancy rates, live birth rates, singleton gestation birth weights, premature birth rates, and neonatal sex ratios were similar between patients with Oligoasthenospermia, OA, and NOA using testicular sperm. This is a provisional file, not the final typeset article Conclusion(s): Regardless of the type of male infertility (oligasthenospermia, OA, NOA) or sperm sources (ejaculate, epididymis, testis), a successful ICSI-ET procedure can result in similar clinical and neonatal outcomes, such as clinical pregnancy rate, live birth rate, abortion rate, neonatal birth weight and sex ratio of singleton pregnancies.